Determination of the Economic Impact of a Traditional Celebration in El Espinal, Oaxaca, Mexico - López Tolentino, Luis Enrique; Ramírez Flores, María Soledad; Hernández Nolasco, Lilián (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To determine the economic impact generated by a traditional isthmian “Vela” in El Espinal, Oaxaca, Mexico. MATERIAL AND METHODS: A cost-benefit analysis was carried out, through the review of financial documents and a survey applied to 120 members, referring to the expense used in the organization and assistance of a traditional Vela. RESULTS: The investigation allowed us to know the economic impact generated by a Vela, an amount that gets to 2,056,456.80, of which 91.37% comes from the indirect effect, while only 8.63% is derived from the direct effect. Consequently, the indirect effect is relatively greater than the direct one. CONCLUSIONS: The economic impact generated by a traditional Vela has a significant effect on the municipality of El Espinal. Most goods and services required to organize and carry out this festivity are provided by formal or informal local commerce and brought about by people from the region. These festivities have also had a great influence on the creation and preservation of trades related to ornament, clothing, food, music, among others.